2015
DOI: 10.1016/j.oraloncology.2015.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic screening of salivary gland mucoepidermoid carcinoma identifies hypomethylation of CLIC3 as a common alteration

Abstract: Objectives The role of promoter methylation in the development of mucoepidermoid carcinoma (MEC) has not been fully explored. In this study, we investigated the epigenetic landscape of MEC. Methods The Illumina HumanMethylation27 BeadChip array and differential methylation analysis were utilized to screen for epigenetic alterations in 14 primary MEC tumors and 14 matched normal samples. Bisulfite sequencing was used to validate these results, with subsequent quantitative Methylation-Specific PCR (qMSP) to va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 31 publications
(30 reference statements)
0
20
0
Order By: Relevance
“…CLIC3 and Rab25 synergistically promote late endosomal/lysosomal integrin cycling and drive cancer progression (Dozynkiewicz et al, 2012). In addition, CLIC3 is highly expressed in mucoepidermoid carcinoma of the salivary gland and promotes tumor progression (Wang et al, 2015). Our study found that CLIC3 is closely linked to BC and analyzed its possibility as a prognostic marker.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…CLIC3 and Rab25 synergistically promote late endosomal/lysosomal integrin cycling and drive cancer progression (Dozynkiewicz et al, 2012). In addition, CLIC3 is highly expressed in mucoepidermoid carcinoma of the salivary gland and promotes tumor progression (Wang et al, 2015). Our study found that CLIC3 is closely linked to BC and analyzed its possibility as a prognostic marker.…”
Section: Discussionmentioning
confidence: 66%
“…CLIC3 can drive cancer progression through glutathionedependent oxidoreductase activity (Hernandez-Fernaud et al, 2017). CLIC3 is highly expressed in a variety of tumors, such as mucoepidermoid carcinoma (Wang et al, 2015) and malignant pleural mesothelioma (Tasiopoulou et al, 2015). However, the expression of CLIC3 in BC has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…85,86,90,91,97,148 Despite the latter, it has been shown that some CRTC1-MAML2 fusion-positive MECs have increased EGFR signaling via amphiregulin (AREG), and that may stimulate growth of MEC. 149 This could provide support for testing/determination of MEC fusion status, if elevated levels of AREG and subsequent activation of AREG-EGFR signaling prove to be a pathway for targeting with anti-EGFR therapy. 150 In MEC, the reported rate of HER2 overexpression appears to be low.…”
Section: Mucoepidermoid Carcinomamentioning
confidence: 99%
“…Hyper-or hypomethylation of DNA may induce the development of tumors by regulating their components, such as proteins of the extracellular matrix, and it can cause chromosomal instability (Dawson & Kouzarides, 2012;Sharma et al, 2010). Epigenetic alterations, isolated or combined, may be involved in the development and progress of SGT (Aniello et al, 2006;Augello et al, 2006;Binmadi et al, 2018;Daa et al, 2008;Durr et al, 2010;Ge et al, 2011;Guimarães et al, 2016;Hu et al, 2011;Kaira et al, 2013;Ling et al, 2016;Nikolic et al, 2018;Schache et al, 2010;Shao et al, 2011Shao et al, , 2012Stephens et al, 2013;Tan et al, 2014;Wagner et al, 2017;Wang et al, 2015;Williams et al, 2006;Xia et al, 2018Xia et al, , 2013Zhang et al, 2007Zhang et al, , 2014.…”
Section: Dna Me Thyl Ati On In Salivary G L and Tumor Smentioning
confidence: 99%
“…Although most studies involve malignant salivary gland tumors, it has been demonstrated that epigenetic alterations may also play a key role in benign salivary gland tumors (Nikolic et al, 2018). Different models and methods have been employed to study these alterations, from cancer stem cell models to tissue from the human biopsy with analysis in genomic level showing the epigenetic landscape of SGT (Nikolic et al, 2018;Sharma et al, 2010;Wang et al, 2015;Zhang et al, 2007). Although there are some studies focused on the comprehensive role of epigenetic alterations in salivary gland tumors, there is no review that synthesizes current literature on this genetic mechanism.…”
mentioning
confidence: 99%